Molecularly imprinted polymers in diagnostics: accessing analytes in biofluids. Issue 37 (13th July 2022) - Mustafa, Yasemin L.; Keirouz, Antonios; Leese, Hannah S.
Abstract : Bio-applied molecularly imprinted polymers (MIPs) are biomimetic materials with tailor-made synthetic recognition sites, mimicking biological counterparts known for their sensitive and selective analyte detection. Abstract : Bio-applied molecularly imprinted polymers (MIPs) are biomimetic materials with tailor-made synthetic recognition sites, mimicking biological counterparts known for their sensitive and selective analyte detection. MIPs, specifically designed for biomarker analysis within biofluids, have the potential to significantly aid patient diagnostics at the point-of-care, enabling self-health monitoring and management. Recent research in this field, facilitated by the hybridisation of materials science and biology, has developed and utilised a variety of different polymerisation synthesis methods tailored to the bio-application of MIPs. This review evaluates the principles of molecular imprinting for disease diagnostics, including recent progress in integrated MIP-sensor technologies for high-affinity analyte detection in complex biofluids from serum and saliva to cerebrospinal fluid, sweat, urine, nasopharyngeal fluid, and tears. The work highlights the state-of-the-art in the progression of MIP-sensor technologies' translation into commercially available sensors and their potential contribution to disease detection systems in healthcare settings.